Practical Pocket Guide to History Taking and Clinical Examination - Williamson; CRC Press LLC. ([S.l.] : CRC Press, 2014)
History taking and examination skills are vitally important in everyday practice. They are examined at all levels of the undergraduate curriculum and are constantly monitored at a postgraduate level. To become proficient in history taking, key questions should be asked to quickly understand the exact nature of the illness.
Chapter 1 General history and examination -- chapter 2 Cardiovascular -- chapter 3 Respiratory -- chapter 4 Gastrointestinal -- chapter 5 Endocrinology -- chapter 6 Haematology -- chapter 7 Renal -- chapter 8 Neurology -- chapter 9 Ear, nose and throat -- chapter 10 Ophthalmology -- chapter 11 Genitourinary -- chapter 12 Gynaecology -- chapter 13 Musculoskeletal -- chapter 14 Skin, nails and hair -- chapter 15 Psychiatry.
Title from content provider.
Added to collection customer.56279.3
Keywords: Physical diagnosis; Medical history taking; Medical history taking; Physical diagnosis; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Electronic book; Electronic books